ChemInform Abstract: Catalytic Asymmetric Aminolactonization of 1, 2‐Disubstituted Alkenoic Acid Esters: Efficient Construction of Aminolactones with an All‐Carbon Quaternary Stereo‐Center. Issue 47 (6th November 2014) - Hajra, Saumen; Akhtar, Sk Md Samim; Aziz, Sk Mohammad
Abstract The title reaction of alkenoic acid esters gives exclusively trans‐γ and δ‐lactones bearing the amino‐functionality with high enantioselectivities.